Applying UML and patterns : - Larman, Craig (Prentice Hall, 1997)
Guides students through each step of requirements, analysis, design, and coding. Topics cover Expressing analysis and design models using the UML, a standard diagramming notation, Applying patterns to assign responsibilities and design collaborations and more. DLC: Object-oriented methods.